Accurate detection of coronary heart disease by new exercise test. Issue 4 (October 1982) - Elamin, M S; Boyle, R; Kardash, M M; Smith, D R; Stoker, J B; Whitaker, W; Mary, D A; Linden, R J
Abstract : The ability of a new exercise test accurately to detect the presence and severity of coronary heart disease has been examined in 206 patients with anginal pain, including patients on beta blockers or with concomitant cardiac lesions. From recordings of 13 electrocardiographic leads during exercise, the maximal rate of progression of ST segment depression relative to increased in heart rate (maximal ST/HR slope) was obtained and used as an index of myocardial ischaemia. The maximal ST/HR slope and results of coronary arteriography were independently obtained and the two sets of data compared the ranges of the maximal ST/HR slopes in the 38 patients with no significant disease, 49 with single vessel, 75 with double vessel, and 44 patients with triple vessel disease were different from each other and there was no overlap in the data between adjacent groups; there were no false positive, false negative, or indeterminate results. It is concluded that the maximal ST/HR slope can be used reliably to predict the presence of absence and severity of coronary heart disease in individual patients presenting with anginal pain in a hospital population.